Dodge Rose - Cox, Jack A. P.; Illinois Arts Council; Australia; Australia Council (Victoria, TX : Dalkey Archive Press, 2016)
Eliza travels to Sydney to deal with the estate of her Aunt Dodge, and finds Maxine, a woman she has never met, occupying Dodge's apartment. When legal complications derail plans to live it up on their inheritance, the women's lives become consumed by absurd attempts to deal with Australian property law, as well their own mounting boredom and squalor.
Includes bibliographical references.
Partially funded by the Illinois Arts Council. This project has been assisted by the Australian Government through the Australia Council for the Arts.
Keywords: Decedents' estates -- New South Wales -- Fiction; Inheritance and succession -- New South Wales -- Fiction; Sydney (N.S.W.) -- Fiction; Australian